Country Reports - Zawati, Ma'n H.; Chalmers, Don; Dallari, Sueli G.; de Neiva Borba, Marina; Pinkesz, Miriam; Joly, Yann; Chen, Haidan; Hartlev, Mette; Leitsalu, Liis; Soini, Sirpa; Rial-Sebbag, Emmanuelle; Hoppe, Nils; et al. (The Journal of law, medicine & ethics, 2019)
Any proposed DTP genomic research would need to comply with the specific requirements of Chapter 3.3 to be satisfactorily addressed for ethical approval. 1.2 The National Health and Medical Research Council has the issue of Direct to Customer Genetic Testing under consideration and has published three relevant information documents.1 1.3 The Commonwealth Australia Government, Department of Health has issued guidance for the Provision of Direct-to-Consumer Genetic Tests: Guiding Principles for Providers.2 The Australian Genomics Health Alliance (AGHA) published a news page on Understanding Direct-to-Consumer Genetic Testing, with information on clinical-grade testing.3 2. There is an over-riding requirement to respect “beliefs, customs and cultural heritage, and local laws” of all participants in other countries.5 The Australian HREC would require approval from the research ethics review body in the other country, where there is one.6 Where there are no “ethics approval processes” in the overseas country, research participants must be “accorded no less respect than [the] National Statement requires,”7 as well as these specific elements for Research generally in Chapter 3.1 and Genomic Research, in particular, as set out in Chapter 3.3.8 As far as is necessary to satisfy the requirements of paragraphs 1.10 to 1.13, the design and conduct of the research should reflect continuing consultation with the local participant population and the communities to which they belong.9 The Australian researcher conducting DTP genomic research in another country must also comply with the Australian Code for the Responsible Conduct of Research, 2018.10 4. Please consider the perspectives of the public, research participants, socially-defined groups (e.g., indigenous or minority populations), researchers, and other professional or government entities. Specific issues with specific research participants, such as socially-defined groups, including as examples indigenous or minority populations, would be critical components of the research design and ethical approval processes.